SPEECH THERAPY TREATMENT OF CHILDREN WITH DEVELOPMENTAL LANGUAGE DISORDER AND ASSOCIATED ATTENTION DEFICIT DISORDER WITH/WITHOUT HYPERACTIVITY - Nuša Novak (The Society for Children with Metabolic Disorders, 2023)
In practice, speech therapists encounter various disorders in communication, speech and language. Individual disorders are often accompanied by mental or physical health disorders, which affect the course of diagnostics and therapy. When working with the child population of speech therapists in practice, we observe an increase in children who, in addition to communication disorder or a speech-language disorder, also have an associated attention disorder with/without hyperactivity. The paper presents a clinical case of a child with developmental language disorder and associated attention disorder who is included in regular speech therapy treatment from 3.3 to 7.2 years old. In the diagnosis process, standardized and non-standardized speech therapy tests were used, which showed the child's deficit in language understanding and expression. Based on the test results, an individualized therapy plan was created, which was based on the stimulation of all language systems. Learning took place through several sensory channels; the combination of auditory-visual stimuli proved to be the most effective approach to mastering a particular skill, and the demonstration method was the most effective work method. The test results on the diagnostic reassessment showed progress in language understanding and expression, and based on clinical observation, progress in the child's attention span is also noticeable.